2021
DOI: 10.1108/md-08-2021-1021
|View full text |Cite
|
Sign up to set email alerts
|

CSR practices and creativity during COVID-19 pandemic in the emerging market: investigating the mediating effect of affective commitment

Abstract: PurposeThis study aims to explore how corporate social responsibility (CSR) dimensions (i.e. economic; legal; ethical; philanthropic) foster employee creativity during the COVID-19 pandemic. Specifically, an attempt is made to investigate the mediating role of affective commitment to explain the above linkage.Design/methodology/approachThe survey data were collected from 167 employees in the emerging market of Saudi Arabia. The data was analysed using PLS-SEM for frequency, reliability, confirmatory factor ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 131 publications
(270 reference statements)
1
20
0
Order By: Relevance
“…There appears to be a wide range of CSR objectives across global merchants in different regions (Mas et al, 2021) during the COVID-19 pandemic. In addition to some research concerning the impact of multiple CSR aspects on pandemic-related creative behaviours, the COVID-19 pandemic, in particular, presents a chance to examine its consequences on consumer' behaviours in the contemporary setting of pandemics often occurring (Mohammed et al, 2021). Therefore, CSR is one of the best strategies and creating a competitive advantage in the value chain (Wu & Kong, 2021) of the retail firms during this pandemic (Goswami & Chouhan, 2021).…”
Section: Covid-19 Csr and Retail Sectormentioning
confidence: 99%
“…There appears to be a wide range of CSR objectives across global merchants in different regions (Mas et al, 2021) during the COVID-19 pandemic. In addition to some research concerning the impact of multiple CSR aspects on pandemic-related creative behaviours, the COVID-19 pandemic, in particular, presents a chance to examine its consequences on consumer' behaviours in the contemporary setting of pandemics often occurring (Mohammed et al, 2021). Therefore, CSR is one of the best strategies and creating a competitive advantage in the value chain (Wu & Kong, 2021) of the retail firms during this pandemic (Goswami & Chouhan, 2021).…”
Section: Covid-19 Csr and Retail Sectormentioning
confidence: 99%
“…We intended our model as a contribution to the slowly emerging picture of the effects of the COVID-19 pandemic on organizational commitment. Based on previously published studies, organizational resilience (Filimonau et al, 2020), organizational support (Alshaabani et al, 2021), and pandemic-induced stress (Kang et al, 2021) out that affective commitment influences organizational psychological variables, such as employees' knowledge application behavior (Ishak et al, 2022) and organizational creativity (Mohammed et al, 2022). The results of our research further highlight how organizational affective commitment is a highly complex notion that depends on many organizational variables, thus organizations and employers need to gain a more profound knowledge and ensure the provision of favorable conditions.…”
Section: Discussion Limitations and Future Workmentioning
confidence: 51%
“…Based on this study, Liu and Jang (2009) showed that satisfaction is highly connected to behavioural intentions. We tested a new mediator in the typical relationship of the food culture attributes and patronage intention, following the direction of Nirino et al (2020) and Mohammed et al (2021); in their studies, they proposed the need for new models and variables to recognise the dynamics of these complex and conflicting relationships. Existing literature provides adequate evidence regarding the satisfaction associated with patronage intention and the positive relationships between flavour, presentation, culinary methods, gastronomic identity and patronage intention.…”
Section: Mediating Role Of Attendees' Satisfactionmentioning
confidence: 99%